genetics of water-use efficiency and its relation to growth in maritime pine - Marguerit, Elisa; Bouffier, Laurent; Chancerel, Emilie; Costa, Paolo; Lagane, Frédéric; Guehl, Jean-Marc; Plomion, Christophe; Brendel, Oliver (Journal of experimental botany, 2014)
To meet the increasing demand of wood biomass worldwide in the context of climate change, developing improved forest tree varieties for high productivity in water-limited conditions is becoming a major issue. This involves breeding for genotypes combining high growth and moderate water loss and thus high water-use efficiency (WUE). The present work provides original data about the genetics of intrinsic WUE (the ratio between net CO2 assimilation rate and stomatal conductance, also estimated by carbon isotope composition of plant material; δ13C) and its relation to growth in Pinus pinaster Ait. First, heritability for δ13C was estimated (0.29) using a 15-year-old progeny trial (Landes provenance), with no significant differences among three sites contrasting in water availability. High intersite correlations (0.63–0.91) and significant but low genotype–environment interactions were detected. Secondly, the genetic architectures of δ13C and growth were studied in a three-generation inbred pedigree, introducing the genetic background of a more-drought-adapted parent (Corsican provenance), at ages of 2 years (greenhouse) and 9 years (plantation). One of the quantitative trait loci (QTLs) identified in the field experiment, explaining 67% of the phenotypic variance, was also found among the QTLs detected in the greenhouse experiment, where it colocalized with QTLs for intrinsic WUE and stomatal conductance. This work was able to show that higher WUE was not genetically linked to less growth, allowing thus genetic improvement of water use. As far as is known, the heritability and QTL effects estimated here are based on the highest number of genotypes measured to date.